The effect of a single early high-dose vitamin D supplement on fracture union in patients with hypovitaminosis D: a prospective randomised trial. (November 2017) - Haines, N.; Kempton, L. B.; Seymour, R. B.; Bosse, M. J.; Churchill, C.; Hand, K.; Hsu, J. R.; Keil, D.; Kellam, J.; Rozario, N.; Sims, S.; Karunakar, M. A.
Abstract : Aims: To evaluate the effect of a single early high-dose vitamin D supplement on fracture union in patients with hypovitaminosis D and a long bone fracture. Patients and Methods: Between July 2011 and August 2013, 113 adults with a long bone fracture were enrolled in a prospective randomised double-blind placebo-controlled trial. Their serum vitamin D levels were measured and a total of 100 patients were found to be vitamin D deficient (< 20 ng/ml) or insufficient (< 30 ng/mL). These were then randomised to receive a single dose of vitamin D3 orally (100 000 IU) within two weeks of injury (treatment group, n = 50) or a placebo (control group, n = 50). We recorded patient demographics, fracture location and treatment, vitamin D level, time to fracture union and complications, including vitamin D toxicity. Outcomes included union, nonunion or complication requiring an early, unplanned secondary procedure. Patients without an outcome at 15 months and no scheduled follow-up were considered lost to follow-up. The t -test and cross tabulations verified the adequacy of randomisation. An intention-to-treat analysis was carried out. Results: In all, 100 (89%) patients had hypovitaminosis D. Both treatment and control groups had similar demographics and injury characteristics. The initial median vitamin D levels were 16 ng/mL (interquartile range 5 to 28) in both groups (p = 0.885). A total of 14 patients were lost to follow-up (seven from each group), two had fixation failure (one in each group) and one control group patient developed an infection. Overall, the nonunion rate was 4% (two per group). No patient showed signs of clinical toxicity from their supplement. Conclusions: Despite finding a high level of hypovitaminosis D, the rate of union was high and independent of supplementation with vitamin D3 . Cite this article: Bone Joint J 2017;99-B:1520–5.